2017
DOI: 10.1371/journal.pgen.1006950
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporter ZIP13 suppresses beige adipocyte biogenesis and energy expenditure by regulating C/EBP-β expression

Abstract: Given the relevance of beige adipocytes in adult humans, a better understanding of the molecular circuits involved in beige adipocyte biogenesis has provided new insight into human brown adipocyte biology. Genetic mutations in SLC39A13/ZIP13, a member of zinc transporter family, are known to reduce adipose tissue mass in humans; however, the underlying mechanisms remains unknown. Here, we demonstrate that the Zip13-deficient mouse shows enhanced beige adipocyte biogenesis and energy expenditure, and shows amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 56 publications
0
29
0
1
Order By: Relevance
“…Therefore, we aimed to clarify the roles of ZIP13 in fat tissue. During our investigation, we found that Zip13 -KO inguinal WAT had a high number of functional beige adipocytes [ 74 ]. Furthermore, Zip13 -KO mice showed a significantly higher oxygen consumption rate than wild-type mice, although there were no differences in food intake, suggesting that Zip13 -KO mice have a tendency to not gain weight.…”
Section: Zinc Distribution Affects Adipocyte Metabolismmentioning
confidence: 99%
“…Therefore, we aimed to clarify the roles of ZIP13 in fat tissue. During our investigation, we found that Zip13 -KO inguinal WAT had a high number of functional beige adipocytes [ 74 ]. Furthermore, Zip13 -KO mice showed a significantly higher oxygen consumption rate than wild-type mice, although there were no differences in food intake, suggesting that Zip13 -KO mice have a tendency to not gain weight.…”
Section: Zinc Distribution Affects Adipocyte Metabolismmentioning
confidence: 99%
“…A peptide derived from VGF (VGF nerve growth factor inducible) helps control insulin secretion (37). DLK1 (Delta Like Non-Canonical Notch Ligand 1) (38) induces insulin synthesis and secretion, and SLC39A13 (Solute Carrier Family 39 Member 13) is a transporter protein for Zn ++ , which could play a role in insulin storage, secretion, and activity (39). In searching for an example of INS expression-dependent interchromosomal transvection that affected insulin metabolism, our attention was drawn to SSTR5-AS1, which codes for an antisense RNA to SSTR5.…”
Section: Expression Levels Of Contacted Genes Affected By Ins Expressionmentioning
confidence: 99%
“…These patients exhibited significantly decreased white fat mass. Recently, Fukunaka et al demonstrated that ZIP13-mediated Zn transport plays a critical role in suppressing adipocyte browning by reducing C/EBP-β proteins [ 84 ], which are discussed in this issue by Fukunaka and Fujitani. The molecular mechanism of the pathogenesis induced by the mutations is described below.…”
Section: Overview Of Mammalian Zrt- and Irt-like Protein (Zip) Tramentioning
confidence: 99%